Electrochemical and Electronic Devices
By optimizing the working lengths of the positive electrode tab and the mass percentage of ring carbonate in the electrolyte, the electrochemical device achieves improved cycle, high temperature, and safety performance for lithium-ion batteries.
Patent Information
- Application Number
- JP2024555960
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-11
- Filing Date
- 2022-09-05
- Publication Date
- 2025-04-16
AI Technical Summary
Lithium-ion batteries face challenges in improving cycle performance, high temperature safety, and overall efficiency while maintaining high energy density and low costs.
The electrochemical device incorporates a positive electrode piece with a positive electrode tab of specific working lengths and an electrolyte containing ring carbonate, optimizing the mass percentage of ring carbonate relative to the electrolyte mass to achieve a synergistic effect that enhances cycling, high temperature, and safety performance.
This configuration improves the overall performance of the electrochemical device by enhancing cycle life, high temperature stability, and safety without compromising dynamic performance or energy density.
Smart Images

Figure 2025511572000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims priority to a Chinese patent application filed with the China Patent Office on May 11, 2022, bearing application number 202210506822.1 and entitled "Electrochemical Device and Electronic Device", the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to the electrochemical technology field, and in particular to electrochemical and electronic devices. [Background technology]
[0003] Lithium ion batteries have the advantages of large energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, high safety, etc., and are widely used in various fields such as portable electric energy storage, electronic devices, electric vehicles, etc., and gradually become the main battery in the above fields. In the rapid development of lithium ion batteries, the requirements for the overall performance of lithium ion batteries are also increasing. For example, how to improve the cycle performance, high temperature performance and safety performance of lithium ion batteries while ensuring that lithium ion batteries have high energy density and low cost, etc., is an urgent task to improve the overall performance of lithium ion batteries. Summary of the Invention
[0004] The present invention aims to provide electrochemical and electronic devices that improve overall performance.
[0005] The first aspect of the present invention provides an electrochemical device, the electrochemical device comprising a positive electrode piece and an electrolyte, the positive electrode piece comprising a positive electrode tab, the working length b of the positive electrode tab being 0.5m to 3m, the electrolyte comprising a cyclic carbonate, the mass percentage of the cyclic carbonate being a% based on the mass of the electrolyte, the cyclic carbonate comprising ethylene carbonate and / or propylene carbonate, the electrochemical device satisfying 13≦a / b≦110, preferably 20≦a / b≦110. By controlling the working length b and a / b values of the positive electrode tab within the above ranges and selecting the cyclic carbonate, a synergistic effect is generated between the positive electrode piece and the electrolyte without affecting the dynamic performance of the electrochemical device, which is advantageous for improving the cycle performance, high temperature performance and safety performance of the electrochemical device, and further improving the overall performance of the electrochemical device.
[0006] Here, along the length of the positive electrode piece, the positive electrode piece includes a first edge and a second edge opposite the first edge, there is one positive electrode tab, a distance from the positive electrode tab to the first edge is L1, a distance from the positive electrode tab to the second edge is L2, and the working length b is equal to the maximum of L1 and L2; or there are two positive electrode tabs, the positive electrode tab closer to the first edge is a first positive electrode tab, and the positive electrode tab closer to the second edge is a second positive electrode tab, a distance from the first positive electrode tab to the first edge is L3, a distance from the second positive electrode tab to the second edge is L4, a distance between the first positive electrode tab and the second positive electrode tab is L5, and the working length b is equal to the maximum of L3, L4, and 0.5×L5.
[0007] In some embodiments of the present invention, 25≦a≦60, 14.5≦a / b≦110. By controlling the values of a and a / b within the above ranges, the safety performance of the electrochemical device can be improved without affecting the kinetic performance of the electrochemical device, and the overall performance of the electrochemical device can be improved.
[0008] In some embodiments of the present invention, the positive electrode piece includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector, and the coating weight of the positive electrode material layer is C g / 1540.25 mm 2 and the electrochemical device satisfies 50≦a / C≦300. By controlling the value of a / C within the above range, the cycle performance, high temperature performance and safety performance of the electrochemical device can be improved without affecting the kinetic performance and energy density of the electrochemical device, and the overall performance of the electrochemical device can be improved.
[0009] In some embodiments of the present invention, 0.2≦C≦0.5. By controlling the value of C within the above range, the safety performance of the electrochemical device can be improved without affecting the energy density of the electrochemical device, and the overall performance of the electrochemical device can be improved.
[0010] In some embodiments of the present invention, the electrolyte solution includes a polynitrile compound, and a mass percentage d% of the polynitrile compound is 0.5% to 5% based on the mass of the electrolyte solution, and the polynitrile compound includes at least one of glutaronitrile, adiponitrile, succinonitrile, crotononitrile, 3-methylbutenenitrile, 1,2-bis(cyanoethoxy)ethane, 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile. Preferably, the electrolyte contains at least one of glutaronitrile, adiponitrile, succinonitrile, and 1,2-bis(cyanoethoxy)ethane, and at least one of 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile. By controlling the mass percentage of the polynitrile compound within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the dynamic performance of the electrochemical device. By selecting the polynitrile compound, it is possible to improve the cycle performance, high temperature performance, and safety performance of the electrochemical device, and further improve the overall performance of the electrochemical device.
[0011] In some embodiments of the present invention, the positive electrode piece comprises a positive electrode active material, and Dv10 of the positive electrode active material and mass percentage d% of the polynitrile compound satisfy the following numerical values: 0.2≦d / Dv10≦4, 1 μm≦Dv10≦5 μm. Controlling the value of d / Dv10 within the above range is favorable for improving the cycle performance, high temperature performance and safety performance of the electrochemical device, and further improves the overall performance of the electrochemical device.
[0012] In some embodiments of the present invention, the electrolyte contains a sulfur-oxygen double bond-containing compound, and the mass percentage of the sulfur-oxygen double bond-containing compound is 0.01% to 8% based on the mass of the electrolyte, and the sulfur-oxygen double bond-containing compound includes at least one of 1,3-propane sultone, ethylene sulfate, methylene methane disulfonate, propenyl-1,3-sultone, tetrafluoroethane-beta-sultone, 2,4-butane sultone, 1,4-butane sultone, 1,8-naphthalene sulfonic acid lactone, and ethylene sulfite. By controlling the mass percentage of the sulfur-oxygen double bond-containing compound within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the kinetic performance of the electrochemical device. By selecting the sulfur-oxygen double bond-containing compound, the cycle performance, high temperature performance, and safety performance of the electrochemical device can be improved, and the overall performance of the electrochemical device can be improved.
[0013] In some embodiments of the present invention, the electrolyte contains a lithium salt additive, and the mass percentage e% of the lithium salt additive is 0.01% to 2% based on the mass of the electrolyte, and the lithium salt additive includes at least one of difluorophosphate lithium, lithium difluorooxalatoborate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium tetraborate, lithium borate, and trifluoromethanesulfonate lithium. By controlling the mass percentage of the lithium salt additive within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the kinetic performance of the electrochemical device. By selecting the lithium salt additive, the cycle performance, high temperature performance, and safety performance of the electrochemical device can be improved, and the overall performance of the electrochemical device can be improved. In some embodiments of the present invention, the positive electrode piece includes a positive electrode material layer, and the positive electrode active material in the positive electrode material layer includes element A, and based on the mass of the positive electrode active material, the mass percentage of element A is 0.001% to 2%, and element A includes at least one of Al, B, Cr, Fe, Mg, Na, S, Ti, Zr, Y, Nb, Mo, W, F and P. This can improve the cycle performance, high temperature performance and safety performance of the electrochemical device, and further improve the overall performance of the electrochemical device.
[0014] A second aspect of the present invention provides an electronic device, comprising the electrochemical device according to any one of the above embodiments. The electrochemical device provided by the present invention has good comprehensive performance, so that the resulting electronic device has a long service life.
[0015] The present invention provides an electrochemical device and an electronic device, the electrochemical device includes a positive electrode piece and an electrolyte, the positive electrode piece includes a positive electrode tab, the working length b of the positive electrode tab is 0.5m-3m, the electrolyte includes a cyclic carbonate, based on the mass of the electrolyte, the mass percentage of the cyclic carbonate is a%, the cyclic carbonate includes ethylene carbonate and / or propylene carbonate, and the electrochemical device satisfies 13≦a / b≦110. By controlling the working length b and the value of a / b of the positive electrode tab within the above range and selecting the cyclic carbonate, a synergistic effect is generated between the positive electrode piece and the electrolyte without affecting the dynamic performance of the electrochemical device, which is favorable to improving the cycle performance, high temperature performance and safety performance of the electrochemical device, and further improving the overall performance of the electrochemical device.
[0016] Of course, it is not necessary for the practice of any one embodiment of the present invention to simultaneously achieve all of the above advantages. [Brief description of the drawings]
[0017] In the following, in order to more clearly describe the technical solutions of the embodiments of the present invention and the prior art, the drawings necessary for the embodiments and the prior art will be briefly described. Obviously, the drawings described below are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without requiring creative efforts. [Figure 1] FIG. 2 is a schematic structural diagram of a positive electrode piece in some embodiments of the present invention. [Diagram 2] FIG. 4 is a schematic structural diagram of a positive electrode piece according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention will be described in more detail with reference to the drawings by way of examples. Of course, the described examples are only a part of the embodiments of the present invention, and are not all of the embodiments. All other embodiments that a person skilled in the art can obtain based on the embodiments of the present invention without creative labor are all within the scope of protection of the present invention.
[0019] In the specific embodiment of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0020] A lithium ion battery generally includes a positive electrode piece, a negative electrode piece, a separator, and an electrolyte, which are all important factors that affect the performance of the lithium ion battery. In a lithium ion battery having a wound structure, when the aspect ratio of the positive electrode piece and the negative electrode piece is large and the number of positive electrode tabs provided on the positive electrode piece is small (e.g., one or two), it affects the uniformity of the current density and temperature distribution in different regions of the positive electrode piece, thereby affecting the overall performance of the lithium ion battery, such as cycle performance, high temperature performance, and safety performance. In view of the above problems, the present invention provides an electrochemical device and an electronic device that improve the overall performance.
[0021] A first aspect of the present invention provides an electrochemical device comprising a positive electrode piece and an electrolyte, the positive electrode piece comprising a positive electrode tab, the active length b of the positive electrode tab being 0.5 m to 3 m, the electrolyte comprising a cyclic carbonate, the mass percentage of the cyclic carbonate being a % based on the mass of the electrolyte, the cyclic carbonate comprising ethylene carbonate (EC) and / or propylene carbonate (PC), the electrochemical device satisfying 13≦a / b≦110, preferably 20≦a / b≦110.
[0022] For ease of understanding, an orthogonal coordinate system is established in which the length direction of the positive electrode piece is the X direction and the width direction of the positive electrode piece is the Y direction. As shown in Figures 1 and 2, along the length direction (X direction) of the positive electrode piece 10, the positive electrode piece 10 includes a first edge 11 and a second edge 12 opposite to the first edge 11. Specifically, as shown in Figure 1, when the positive electrode piece 10 has one positive electrode tab 20, the distance from the positive electrode tab 20 to the first edge 11 is L1, the distance from the positive electrode tab 20 to the second edge 12 is L2, and the active length b of the positive electrode tab is equal to the maximum value of L1 and L2. Or, as shown in FIG. 2, in the case where there are two positive electrode tabs 20 on the positive electrode piece 10, the positive electrode tab 20 closer to the first edge 11 is the first positive electrode tab 21, and the positive electrode tab 20 closer to the second edge 12 is the second positive electrode tab 22, the distance from the first positive electrode tab 21 to the first edge 11 is L3, the distance from the second positive electrode tab 22 to the second edge 12 is L4, the distance between the first positive electrode tab 21 and the second positive electrode tab 22 is L5, and the active length b of the positive electrode tabs is equal to the maximum value of L3, L4, and 0.5×L5.
[0023] The applicant of the present invention found that if the value of a / b is too small (e.g., less than 13) or the working length b of the positive electrode tab is too large (e.g., more than 3 m), the current density and heat quantity in the positive electrode piece will be non-uniform, and the current density will be high in the area close to the positive electrode tab, and the heat will be concentrated and the temperature will be high, which will increase the amount of lithium released, and the phenomenon of lithium deposition will easily occur in the negative electrode piece, and will lead to the progression of structural collapse of the positive electrode active material in the positive electrode piece, and will further lead to the progression of side reactions between the positive electrode active material and the electrolyte, which will affect the cycle performance and safety performance of the electrochemical device, and even lead to failure of the electrochemical device. If the value of a / b is too large (e.g., more than 110), the relative content of cyclic carbonate will be high, which will limit the improvement of lithium ion transfer by the electrolyte, and will easily cause the phenomenon of lithium deposition in the negative electrode piece, which will affect the dynamic performance (e.g., rate performance) and safety performance of the electrochemical device. By controlling the working length b and the value of a / b of the positive electrode tab within the above range and selecting the cyclic carbonate having good chemical stability and thermal stability, a synergistic effect is generated between the positive electrode piece and the electrolyte without affecting the dynamic performance of the electrochemical device, and the cycle performance, high temperature performance, safety performance, etc. of the electrochemical device can be improved, and the overall performance of the electrochemical device can be improved. For example, the working length b of the positive electrode tab may be 0.5m, 1m, 1.5m, 2m, 2.5m, 3m, or a range between any two of the above values, and the value of a / b may be 13, 20, 30, 40, 50, 60, 70, 80, 90, 10, 110, or a range between any two of the above values. When the electrolyte contains EC and PC simultaneously, the present invention does not particularly limit the mass ratio of EC and PC, as long as the object of the present invention can be achieved. For example, the mass ratio of EC and PC may be 1:5 to 4:1.
[0024] In some embodiments of the present invention, 25≦a≦60, 14.5≦a / b≦110. Specifically, the value of a / b is within the above range, but if the value of a is too small (e.g., less than 25), i.e., the mass percentage of cyclic carbonate is too low, it is not favorable to form a good protective interface on the surface of the positive electrode piece to reduce the side reaction between the positive electrode active material and the electrolyte, thereby affecting the cycle performance of the electrochemical device, and is also not favorable to improving the high temperature performance of the electrochemical device. If the value of a is too large (e.g., more than 60), i.e., the mass percentage of cyclic carbonate is too high, the viscosity of the electrolyte increases, which affects the transfer of lithium ions and is easy to cause the phenomenon of lithium precipitation on the negative electrode piece, thereby affecting the dynamic performance and safety performance of the electrochemical device. By controlling the value of a within the above range, the cyclic carbonate has a suitable mass percentage, which is favorable for forming a suitable protective interface on the surface of the positive electrode piece, so as to reduce the side reaction between the positive electrode active material and the electrolyte, and at the same time, can passivate the interface of the lithium deposition part of the negative electrode piece, and can improve the safety performance of the electrochemical device without affecting the dynamic performance of the electrochemical device, and further improve the overall performance of the electrochemical device. For example, the value of a can be 25, 30, 35, 40, 45, 50, 55, 60, or a range between any two of the above values.
[0025] In some embodiments of the present invention, the positive electrode piece includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector, and the coating weight of the positive electrode material layer is C g / 1540.25 mm 2and the electrochemical device satisfies 50≦a / C≦300. When a / C satisfies the above range, the electrochemical device can improve the concentration polarization of the positive electrode material layer between the positive electrode collector side and the separator side without impairing the energy density, thereby reducing the phenomenon of locally large current density in the thickness direction of the positive electrode piece, local overheating due to polarization problems, phase change of the material, and lithium deposition of the negative electrode piece, thereby improving the safety performance, cycle performance, and high temperature performance of the electrochemical device. By controlling the value of a / C within the above range, the cycle performance, high temperature performance, and safety performance of the electrochemical device can be improved without affecting the kinetic performance and energy density of the electrochemical device, and the overall performance of the electrochemical device can be improved. For example, the value of a / C may be 50, 100, 150, 175, 200, 250, 300, or a range between any two of the above values. The at least one surface of the positive electrode collector is at least one surface of both surfaces along the thickness direction of the positive electrode collector.
[0026] In some embodiments of the present invention, 0.2≦C≦0.5. Specifically, the positive electrode piece satisfies 0.2≦C≦0.5, so as to ensure the energy density and maintain the transfer efficiency of ions and electrons in the positive electrode material layer. By controlling the value of C within the above range, the positive electrode material layer has a suitable coating mass, so that the safety performance of the electrochemical device can be improved without affecting the energy density of the electrochemical device, and the overall performance of the electrochemical device can be improved. For example, the value of C can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or a range between any two of the above values.
[0027] In some embodiments of the present invention, the electrolyte comprises a polynitrile compound, and the mass percentage d% of the polynitrile compound is 0.5% to 5% based on the mass of the electrolyte, and the polynitrile compound comprises at least one of glutaronitrile, adiponitrile (ADN), succinonitrile (SN), crotononitrile, 3-methylbutenenitrile, 1,2-bis(cyanoethoxy)ethane (DENE), 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile (HTCN), 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile. Preferably, the electrolyte contains at least one of glutaronitrile, adiponitrile, succinonitrile, and 1,2-bis(cyanoethoxy)ethane, and at least one of 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile. The addition of the polynitrile compound to the electrolyte is advantageous in suppressing the phase change of the positive electrode active material, and therefore reduces the side reaction between the positive electrode active material and the electrolyte, so as to further improve the safety performance and cycle performance of the electrochemical device, and further improve the overall performance of the electrochemical device. Specifically, if the mass percentage of the polynitrile compound is too low (e.g., less than 0.5%), the improvement in the cycle performance and safety performance of the electrochemical device is not significant. If the mass percentage of the polynitrile compound is too high (e.g., more than 5%), the viscosity of the electrolyte increases, which affects the transfer of lithium ions and is prone to cause the phenomenon of lithium precipitation on the negative electrode piece, thereby affecting the dynamic performance and safety performance of the electrochemical device. By controlling the mass percentage of the polynitrile compound within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the dynamic performance of the electrochemical device. For example, the mass percentage of the polynitrile compound may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two of the above values.By selecting the polynitrile compound, it is more advantageous to improve the stability of the positive electrode active material, and a synergistic effect is generated between the polynitrile compound and the cyclic carbonate, which improves the cycle performance, high temperature performance, and safety performance of the electrochemical device, and further improves the overall performance of the electrochemical device.
[0028] In some embodiments of the present invention, the positive electrode piece includes a positive electrode active material, and the Dv10 of the positive electrode active material and the mass percentage d% of the polynitrile compound satisfy the following numerical values: 0.2≦d / Dv10≦4, 1 μm≦Dv10≦5 μm. By controlling the values of d / Dv10 and Dv10 within the above ranges, it is advantageous to generate a synergistic effect between the electrolyte and the positive electrode piece, and thus the cycle performance, high temperature performance, safety performance, etc. of the electrochemical device can be improved, and the overall performance of the electrochemical device can be further improved. For example, the value of d / Dv10 can be 0.2, 0.4, 0.8, 1.2, 1.6, 2.0, 2.5, 3.0, 3.5, 4.0, or any range between the two values, and the value of Dv10 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range between the two values. Dv10 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 10%.
[0029] In some embodiments of the present invention, the electrolyte contains a sulfur-oxygen double bond-containing compound, and the mass percentage of the sulfur-oxygen double bond-containing compound is 0.01% to 8% based on the mass of the electrolyte, and the sulfur-oxygen double bond-containing compound includes at least one of 1,3-propane sultone (PS), ethylene sulfate (DTD), methylene disulfonate (MMDS), propenyl-1,3-sultone (PES), tetrafluoroethane-beta-sultone, 2,4-butane sultone, 1,4-butane sultone, 1,8-naphthalenesulfonic acid lactone, and ethylene sulfite. The addition of the sulfur-oxygen double bond-containing compound to the electrolyte can improve the stability of the protective interface on the surface of the positive electrode piece and improve the stability of the positive electrode active material, thereby suppressing the phase change of the positive electrode active material and the side reaction between the positive electrode active material and the electrolyte, further improving the safety performance and cycle performance of the electrochemical device, and further improving the overall performance of the electrochemical device. Specifically, when the mass percentage of the sulfur-oxygen double bond-containing compound is low (e.g., less than 0.01%), the improvement in cycle performance and safety performance of the electrochemical device is not significant. When the mass percentage of the sulfur-oxygen double bond-containing compound is high (e.g., more than 8%), the protective interface formed on the surface of the positive electrode piece and the surface of the negative electrode piece is too dense, which affects the transfer of lithium ions, and thus affects the dynamic performance of the electrochemical device. By controlling the mass percentage of the sulfur-oxygen double bond-containing compound within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the dynamic performance of the electrochemical device. For example, the mass percentage of the sulfur-oxygen double bond-containing compound may be 1%, 2%, 3%, 4%, 4.5%, 5%, 6%, 7%, 8%, or a range between any two of the above values. The selection of the sulfur-oxygen double bond-containing compound is more advantageous in improving the stability of the positive electrode active material, and also produces a synergistic effect between the sulfur-oxygen double bond-containing compound and the cyclic carbonate, thereby improving the cycle performance, high temperature performance, and safety performance of the electrochemical device, and further improving the overall performance of the electrochemical device.
[0030] In some embodiments of the present invention, the electrolyte comprises a sulfur-oxygen double bond-containing compound, and the mass percentage of the sulfur-oxygen double bond-containing compound is 0.5%-5% based on the mass of the electrolyte. The sulfur-oxygen double bond-containing compound comprises propenyl-1,3-sultone (PES), and the mass percentage of the propenyl-1,3-sultone is 0.5%-2% based on the mass of the electrolyte. When the electrochemical device satisfies 13≦a / b≦110, adding propenyl-1,3-sultone (PES) to the electrolyte has a significant inhibitory effect on the locally high current density in the positive electrode piece and the phase change of the positive electrode active material due to the polarization effect, so that the cycle performance, high temperature storage performance and float charge expansion rate of the electrochemical device can be further improved.
[0031] In some embodiments of the present invention, the electrolyte contains a lithium salt additive, and based on the mass of the electrolyte, the mass percentage e% of the lithium salt additive is 0.01% to 2%, preferably 0.01% to 1%, and the lithium salt additive is lithium difluorophosphate (LiPO 2 F 2 ), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF 4 ), lithium tetraborate (B 4 Li 2 O 7 ), lithium borate (Li 3 BO 3 ), and lithium trifluoromethanesulfonate (CF 3 LiO 3S). When the electrochemical device satisfies 13≦a / b≦110, adding the lithium salt additive to the electrolyte can improve the stability of the positive electrode electrolyte interface on the surface of the positive electrode piece and improve the stability of the positive electrode active material, thereby suppressing the phase change of the positive electrode active material in the long positive electrode piece and the side reaction between the positive electrode active material and the electrolyte. A stable solid electrolyte interface is formed on the surface of the negative electrode piece, suppressing the side reaction between the electrolyte and the negative electrode active material, further improving the safety performance and cycle performance of the electrochemical device, and further improving the overall performance of the electrochemical device. Specifically, when the mass percentage of the lithium salt additive is low (e.g., less than 0.01%), the improvement in the cycle performance and safety performance of the electrochemical device is not significant. When the mass percentage of the lithium salt additive is high (e.g., more than 2%), the density of the solid electrolyte interface formed on the surface of the negative electrode piece is too high, which affects the transfer of lithium ions, thereby affecting the dynamic performance of the electrochemical device. By controlling the mass percentage of the lithium salt additive within the above range, it is advantageous to improve the safety performance and cycle performance of the electrochemical device without affecting the dynamic performance of the electrochemical device. For example, the mass percentage of the lithium salt additive may be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, or a range between any two of the above values. By selecting the lithium salt additive, it is more advantageous to improve the stability of the positive electrode active material and the stability of the solid electrolyte interface, and a synergistic effect is generated between the lithium salt additive and the cyclic carbonate, which improves the cycle performance, high temperature performance, and safety performance of the electrochemical device, and further improves the overall performance of the electrochemical device.
[0032] In some embodiments of the present invention, the positive electrode piece includes a positive electrode material layer, and the positive electrode active material in the positive electrode material layer includes element A, and the mass percentage of element A is 0.001% to 2%, preferably 0.05% to 0.5%, based on the mass of the positive electrode active material, and element A includes at least one of Al, B, Cr, Fe, Mg, Na, S, Ti, Zr, Y, Nb, Mo, W, F and P. By introducing the element A into the positive electrode active material and controlling the mass percentage of element A within the above range, it is advantageous to generate a synergistic effect between the positive electrode active material and the electrolyte in any one of the above embodiments, so that the cycle performance, high temperature performance and safety performance of the electrochemical device can be improved, and the overall performance of the electrochemical device can be further improved. Here, the present invention is not particularly limited to the positive electrode active material, as long as it can achieve the object of the present invention. For example, the positive electrode active material may include at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, and lithium iron phosphate, but is not limited thereto. As will be understood, the positive electrode active material may include the element A. The present invention is not particularly limited with respect to the Dv50 and Dv90 of the positive electrode active material, as long as the object of the present invention can be achieved. For example, the Dv50 of the positive electrode active material is 0.4 μm to 20 μm, and the Dv90 is 2 μm to 40 μm. Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%, and Dv90 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 90%.
[0033] The present invention is not particularly limited to the method for producing a positive electrode active material containing element A, as long as it can achieve the object of the present invention. For example, the method for producing a positive electrode active material containing element A may include, but is not limited to, a step of mixing materials for producing a positive electrode active material containing element A and then calcining to obtain a positive electrode active material containing element A. Here, the introduction method of element A is to add an oxide of element A as a material, and the oxide of element A may be mixed and added together with other materials at first, or may be added during calcination. Here, the mass percentage of element A in the positive electrode active material is realized by controlling the amount of oxide of element A added. Usually, when the amount of oxide of element A added increases, the mass percentage of element A in the positive electrode active material also increases, and when the amount of oxide of element A added decreases, the mass percentage of element A in the positive electrode active material also decreases. The materials for producing the positive electrode active material containing element A and the content ratio between each material can be selected according to the positive electrode active material containing element A that is actually required, but the present invention is not limited thereto. The temperature and time of the calcination may be any temperature and time known in the art for producing a positive electrode active material, but the present invention is not limited thereto. The oxide of element A is the most common oxide among all oxides of element A when producing a positive electrode active material.
[0034] In the present invention, the positive electrode material layer is provided on at least one of the two surfaces in the thickness direction of the positive electrode current collector, but as will be understood, the "surface" here may be the entire region of the positive electrode current collector, or may be a partial region of the positive electrode current collector, and the present invention is not particularly limited as long as the object of the present invention can be achieved. In the present invention, the positive electrode current collector is not particularly limited as long as the object of the present invention can be achieved. The positive electrode current collector may include, for example, aluminum foil, aluminum alloy foil, or a composite current collector, but is not limited thereto. The positive electrode current collector is preferably an aluminum foil. In the present invention, the thickness of the positive electrode current collector is not particularly limited as long as the object of the present invention can be achieved. For example, the thickness of the positive electrode current collector is 1 μm to 30 μm, preferably 5 μm to 12 μm.
[0035] In the present invention, the positive electrode material layer may further include a binder. The binder of the present invention is not particularly limited, and may be any binder that can achieve the object of the present invention. The binder may include, but is not limited to, at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyvinylpyrrolidone, polyaniline, polyimide, polyamideimide, polysiloxane, styrene butadiene rubber, epoxy resin, polyester resin, polyurethane resin, and polyfluorene.
[0036] In the present invention, the positive electrode material layer may further include a conductive agent. The present invention is not particularly limited to the conductive agent, and it is sufficient if the object of the present invention can be achieved. The conductive agent may include, for example, at least one of natural graphite, sheet graphite, artificial graphite, conductive carbon black (SuperP), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials, and conductive polymers, but is not limited thereto. The carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The carbon fibers may include, but are not limited to, vapor grown carbon fibers (VGCF) and / or nano carbon fibers. The metal materials may include, but are not limited to, metal powder and / or metal fibers. Specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, and silver. The conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene, and polypyrrole.
[0037] The present invention is not particularly limited to the contents of the positive electrode active material, conductive agent, and binder in the positive electrode material layer, and may adopt the contents known in the art. For example, the mass ratio of the positive electrode active material, conductive agent, and binder may be (78-99):(0.1-10):(0.1-10).
[0038] Optionally, the positive electrode piece may further include a conductive layer located between the positive electrode current collector and the positive electrode material layer. The present invention is not particularly limited to the composition of the conductive layer, and may be a common conductive layer in the field. The conductive layer may include, for example, but is not limited to, the conductive agent and the binder.
[0039] In the present invention, the electrochemical device may include the negative electrode piece. The negative electrode piece generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer may be provided on one surface in the thickness direction of the negative electrode collector, or may be provided on two surfaces in the thickness direction of the negative electrode collector. In addition, the "surface" here may be the entire region of the negative electrode collector, or may be a part of the region of the negative electrode collector, and the present invention is not particularly limited as long as the object of the present invention can be achieved. The present invention is not particularly limited to the negative electrode collector, and it is sufficient to achieve the object of the present invention. The negative electrode collector may include, for example, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, carbon-based collector, or composite collector, but is not limited thereto. In the present invention, there is no particular limit to the thickness of the negative electrode collector, and it is sufficient to achieve the object of the present invention. The thickness of the negative electrode collector is, for example, 4 μm to 12 μm.
[0040] In the present invention, the negative electrode material layer includes a negative electrode active material. The negative electrode active material is not particularly limited as long as it can achieve the object of the present invention. The negative electrode active material may include at least one of graphite, hard carbon, silicon, silicon monoxide, and silicone, but is not limited thereto.
[0041] In the present invention, the negative electrode material layer may further include a conductive agent. The conductive agent of the present invention is not particularly limited as long as it can achieve the object of the present invention. The conductive agent of the present invention may include, for example, at least one of the conductive agents described above, but is not limited thereto.
[0042] In the present invention, the negative electrode material layer may further include a binder. The present invention is not particularly limited to the binder, as long as the object of the present invention can be achieved. The binder of the present invention may include, for example, at least one of the binders described above, but is not limited thereto.
[0043] The present invention is not particularly limited to the contents of the negative electrode active material, conductive agent, and binder in the negative electrode material layer, and may adopt the contents known in the art. For example, the mass ratio of the negative electrode active material, conductive agent, and binder may be (78 to 98.5):(0.1 to 10):(0.1 to 10).
[0044] Optionally, the negative electrode further includes a conductive layer located between the negative electrode current collector and the negative electrode material layer. The present invention does not have any particular limitations on the composition of the conductive layer, and the conductive layer may be a common conductive layer in the field. The conductive layer may include, but is not limited to, the conductive agent and the binder.
[0045] In some embodiments, the electrolyte may further include a PO bond-containing compound. The PO bond-containing compound may include, but is not limited to, at least one of tris(trimethylsilane)phosphate (TMSP), tris(trimethylsilane)phosphite (TTSPi), triallyl phosphate, tripropargyl phosphate, triallyl phosphite, and tripropargyl phosphite. Based on the mass of the electrolyte, the mass percentage of the PO bond-containing compound is 0.1% to 10%.
[0046] In the present invention, the electrolyte further includes a non-aqueous solvent. The non-aqueous solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound, and other organic solvents, but is not limited thereto. The carbonate compound may include a chain carbonate compound and / or a fluorocarbonate compound, but is not limited thereto. The chain carbonate compound may include at least one of ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC), but is not limited thereto. The fluorocarbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate. The carboxylate compound may include, but is not limited to, at least one of methyl acetate, ethyl acetate, n-propyl acetate, t-butyl acetate, methyl propionate, ethyl propionate (EP), propyl propionate (PP), gamma-butyrolactone, decalactone, valerolactone, mevalonolactone, caprolactone, and methyl formate. The ether compound may include, but is not limited to, at least one of dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran.Other organic solvents may include, but are not limited to, at least one of dimethylsulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate. Based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 40% to 75%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or a range between any two of the above values.
[0047] In the present invention, the electrolyte may further contain a lithium salt. The present invention is not particularly limited to the lithium salt, and it is sufficient to achieve the object of the present invention. The lithium salt is, for example, LiPF 6 , LiClO 4 , LiB(C 6 H 5 ) 4 , LiCH 3 SO 3 , LiN(SO 2 CF 3 ) 2 , LiC(SO 2 CF 3 ) 3 , LiSiF 6 and lithium difluoroborate. Preferably, the lithium salt is LiPF 6 Includes.
[0048] In the present invention, the density of the electrolyte is 1.10 g / mL to 1.35 g / mL, preferably 1.15 g / mL to 1.30 g / mL. When the density of the electrolyte is within the above range, the electrolyte can better meet the requirements for lithium ion transfer during charging and discharging of the electrochemical device.
[0049] In the present invention, the electrochemical device may include a separator. The material of the separator may include at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide, and aramid, but is not limited thereto. The material of the separator is preferably polyethylene and / or polypropylene. For example, the polyethylene may include at least one of high density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene, but is not limited thereto. The separator of the present invention may have a porous structure. The size of the pore diameter is not particularly limited as long as the object of the present invention can be achieved. For example, the size of the pore diameter of the separator may be 0.01 μm to 1 μm. In the present invention, the thickness of the separator is not particularly limited as long as the object of the present invention can be achieved. The thickness of the separator may be, for example, 5 μm to 500 μm.
[0050] Optionally, the surface of the separator may further include a porous layer. The porous layer is provided on one surface in the thickness direction of the separator substrate, and may be provided on two surfaces in the thickness direction of the separator substrate. The "surface" here may be the entire region of the separator, or a partial region of the separator, and the present invention is not particularly limited as long as the object of the present invention can be achieved. The porous layer includes inorganic particles and a porous layer binder. The inorganic particles are aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), magnesium oxide (MgO), titanium oxide (TiO 2 ), hafnium oxide (HfO 2 ), tin oxide (SnO 2 ), cerium oxide (CeO 2 ), Nickel oxide (NiO), Zinc oxide (ZnO), Calcium oxide (CaO), Zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The porous layer binder may include, but is not limited to, at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, sodium carboxymethylcellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The porous layer on the separator surface can improve the heat resistance, oxidation prevention, and electrolyte infiltration performance of the separator, and can improve the adhesion between the separator and the positive or negative electrode pieces.
[0051] The manufacturing process of the electrochemical device is well known to those skilled in the art, and the present invention is not particularly limited. The manufacturing process of the electrochemical device may include, for example, but is not limited to, the following steps. That is, the positive electrode pieces, the separator, and the negative electrode pieces are stacked in order, and if necessary, the electrode module having a wound structure is obtained by winding, folding, and other operations, and the electrode module is placed in an outer bag, and the electrolyte is injected into the outer bag and sealed to obtain an electrochemical device. Or, the positive electrode pieces, the separator, and the negative electrode pieces are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode module having a stacked structure, and the electrode module is placed in an outer bag, and the electrolyte is injected into the outer bag and sealed to obtain an electrochemical device. In addition, an overcurrent prevention element, a guide plate, and the like can be placed in the outer bag as necessary to prevent the pressure inside the electrochemical device from increasing and overcharging and discharging.
[0052] A second aspect of the present invention provides an electronic device, comprising the electrochemical device according to any one of the above embodiments. The electrochemical device provided by the present invention has good comprehensive performance, and the resulting electronic device has a long service life.
[0053] The electronic device of the present invention is not particularly limited and may be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a portable facsimile, a portable copy machine, a portable printer, a stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini CD, a walkie-talkie, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, a bicycle assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a strobe, a camera, a large household battery, and a lithium ion capacitor.
[0054] Working Example Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Each test and evaluation is performed by the following method. In addition, "%" is mass percentage unless otherwise specified.
[0055] Test methods and equipment Cycle Performance Test The lithium-ion battery was placed in a 45°C incubator and left to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. After the temperature had stabilized, the lithium-ion battery was charged at a constant current of 1C to a voltage of 4.35V, then charged at a constant voltage of 4.35V to a current of 0.05C, and then discharged at a constant current of 1C to a voltage of 2.8V, which was one charge-discharge cycle. The capacity of the initial discharge was taken as 100%. The charge-discharge cycle was repeated, and when the discharge capacity was attenuated to 80%, the test was stopped, and the number of cycles at this time was recorded as the number of cycles at 45°C, which was used as an index to evaluate the cycle performance of the lithium-ion battery.
[0056] High temperature storage performance test The lithium-ion battery was placed in a 25°C incubator and left to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. It was charged to 4.35V at a constant current of 1C, charged to a constant voltage of 0.05C, and then discharged to 2.8V at a constant current of 1C. It was then charged to 4.35V at a constant current of 0.5C, and charged to a constant voltage of 0.05C. The thickness of the battery was measured with a micrometer and recorded as the initial thickness. The test lithium-ion battery was transferred to a 70°C incubator and stored for 48 hours, during which the thickness of the lithium-ion battery was measured and recorded every 6 hours. After storing for 48 hours, the lithium-ion battery was transferred to a 25°C incubator, left to stand for 60 minutes, and discharged to 2.8V at a constant current of 1C. The discharge capacity was recorded and used as the remaining capacity of the lithium-ion battery. The battery was charged to 4.35V at a constant current of 1C, charged at a constant voltage until the current reached 0.05C, and then discharged to 2.8V at a constant current of 1C. The discharge capacity was recorded as the recoverable capacity of the lithium-ion battery, and the thickness of the lithium-ion battery at this time was recorded as the post-test thickness, and the storage thickness expansion rate was calculated as an index for evaluating the amount of high-temperature storage gas generated by the lithium-ion battery. Storage thickness expansion rate = (post-test thickness - initial thickness) / initial thickness x 100%.
[0057] Overcharge Test (1) Overcharge test at 3C and 4.6V The lithium ion battery was discharged at 0.5C at 25°C to 2.8V, then charged at a constant current of 3C to 4.6V, and further charged at a constant voltage for 2 hours, and the temperature change on the surface of the lithium ion battery was monitored. If the lithium ion battery did not ignite, burn, or explode, it was recorded as having passed the test. For each example and comparative example, 10 lithium ion batteries were tested, and the number that passed was recorded.
[0058] (2) Overcharge test at 3C and 4.8V The lithium ion battery was discharged at 0.5C at 25°C to 2.8V, then charged at a constant current of 3C to 4.8V, and further charged at a constant voltage for 2 hours, and the temperature change on the surface of the lithium ion battery was monitored. If the lithium ion battery did not ignite, burn, or explode, it was recorded as having passed the test. For each example and comparative example, 10 lithium ion batteries were tested, and the number that passed was recorded.
[0059] (3) Overcharge test at 3C and 5.4V The lithium ion battery was discharged at 0.5C at 25°C to 2.8V, then charged at a constant current of 3C to 5.4V, and further charged at a constant voltage for 2 hours, and the temperature change on the surface of the lithium ion battery was monitored. If the lithium ion battery did not ignite, burn, or explode, it was recorded as having passed the test. For each example and comparative example, 10 lithium ion batteries were tested, and the number that passed was recorded.
[0060] Hot Box Testing The lithium ion battery was charged at 25°C with a constant current of 0.5C up to 4.35V, and further charged at a constant voltage of 4.35V until the current was 0.05C or less. The fully charged lithium ion battery was placed in a high / low temperature box and heated to 130°C at a rate of 5°C / min. The temperature was kept constant at 130°C for 1 hour, and the lithium ion battery was monitored. If the lithium ion battery did not ignite or explode, it was recorded as having passed the test. For each example and comparative example, 10 lithium ion batteries were tested, and the number that passed was recorded.
[0061] Float charge test The lithium-ion battery was placed in a 25°C incubator and left for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The battery was charged at a constant current of 1C until the voltage reached 4.35V, and then charged at a constant voltage until the current reached 0.05C. The thickness of the lithium-ion battery was measured with a micrometer and recorded as the initial thickness. The test lithium-ion battery was transferred to a 45°C incubator and charged at a current of 1C for 60 days. After the test, the lithium-ion battery was transferred to a 25°C incubator and the thickness of the lithium-ion battery was measured and recorded as the thickness after 60 days of float charging. The float charging thickness expansion rate during the float charging test of the lithium-ion battery was calculated and used as an index to evaluate the float charging performance of the lithium-ion battery. The float charging thickness expansion rate = (thickness after 60 days of float charging - initial thickness) / initial thickness x 100%.
[0062] Particle Size Test The Dv10 of the positive electrode active material was measured using a laser particle size analyzer (e.g., Malvern Master Size 3000) with reference to the Chinese national standard GB / T19077-2016 ("Particle Size Distribution Laser Diffraction Method").
[0063] Example 1-1 <Production of Positive Electrode Pieces> Positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O 2 The conductive carbon black, which is a conductive agent, and the polyvinylidene fluoride, which is a binder, were mixed in a mass ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) was added, and the mixture was stirred uniformly with a vacuum stirrer to obtain a positive electrode slurry with a solid content of 70 wt%. The positive electrode slurry was uniformly applied to one surface of an aluminum foil, which was a positive electrode current collector with a thickness of 10 μm, and the aluminum foil was dried at 85°C for 1 hour to obtain a positive electrode piece with a positive electrode material layer applied on one side. The applied mass of the positive electrode material layer was 0.3 g / 1540.25 mm. 2The above steps were repeated on the other surface of the aluminum foil to obtain a positive electrode piece coated with a positive electrode material layer on both sides. The piece was dried under vacuum conditions at 85°C for 1 hour, and then cold-rolled, cut, and slit to obtain a positive electrode piece with a specification of 65mm x 2010mm. In addition, one positive electrode tab was welded to the positive electrode piece. The working length b of the positive electrode tab was 2m, and the width of the positive electrode tab along the length direction of the positive electrode piece was 10mm. The Dv10 of the positive electrode active material was 2.5μm.
[0064] <Production of negative electrode pieces> The negative electrode active material artificial graphite, the conductive agent conductive carbon black, the thickener sodium carboxymethylcellulose, and the binder styrene butadiene rubber were mixed in a mass ratio of 96.4:1.5:0.5:1.6, deionized water was added, and the mixture was uniformly stirred with a vacuum stirrer to obtain a negative electrode slurry with a solid content of 54 wt%. The negative electrode slurry was uniformly applied to one surface of a copper foil as a negative electrode current collector with a thickness of 7 μm, and the copper foil was dried at 85 ° C to obtain a negative electrode piece with a negative electrode material layer with a thickness of 50 μm applied on one side. The above steps were repeated on the other surface of the copper foil to obtain a negative electrode piece with a negative electrode material layer applied on both sides. The negative electrode piece was dried under vacuum conditions at 85 ° C for 1 hour, and then cold-rolled, cut, and slit to obtain a negative electrode piece with a specification of 68 mm x 2015 mm. Along the length direction of the negative electrode piece (the same as the length direction of the positive electrode piece), the width of the negative electrode tab was 15 mm.
[0065] <Preparation of electrolyte> In an argon gas atmosphere glove box with a water content of less than 10 ppm, EC, PC, EMC, and DEC were mixed in a mass ratio of 10:20:20:50 to obtain an organic solvent. 6 was added to an organic solvent to obtain an electrolyte solution. The mass percentage of the lithium salt was 12.5%.
[0066] <Separator manufacturing> A porous polyethylene film (manufactured by Celgard) having a thickness of 7 μm was used.
[0067] <Lithium-ion battery manufacturing> The positive electrode pieces, separator, and negative electrode pieces prepared above were stacked in order, with a separator between the positive electrode pieces and the negative electrode pieces to serve as an insulator, and then wound up to obtain an electrode module. The electrode module was placed in an aluminum plastic film outer bag, dried, and then an electrolyte was injected. The lithium-ion battery was obtained through processes such as vacuum sealing, standing, chemical formation, degassing, and trimming.
[0068] Examples 1-2 to 1-11, 1-13 and 1-14 It was the same as Example 1-1, except that the relevant manufacturing parameters were adjusted according to Table 1. When b was 0.5m, 1m, and 3m, the size of the positive electrode piece was adjusted in the order of 65mm×510mm, 65mm×1010mm, and 65mm×3010mm, and the size of the negative electrode piece was adjusted in the order of 68mm×515mm, 68mm×1015mm, and 68mm×3015mm.
[0069] Examples 1-12 The same as Example 1-1 except that two tabs were welded to each of the positive and negative electrode pieces, the size of the positive electrode piece was 65 mm x 2030 mm, the size of the negative electrode piece was 65 mm x 2040 mm, L3 was 10 mm, L4 was 1000 mm, and L5 was 1000 mm.
[0070] Examples 1-15 and 1-16 The same as Example 1-1, except that the positive electrode active material was changed to lithium cobalt oxide, and the relevant manufacturing parameters were adjusted according to Table 1.
[0071] Example 2-1, Example 2-2 and Example 2-4 The same as in Examples 1-3, except that the relevant production parameters were adjusted according to Table 2.
[0072] Example 2-3 The same as Examples 1-8, except that the relevant production parameters were adjusted according to Table 2.
[0073] Examples 3-1 to 3-11 The same procedure as in Example 1-3 was followed, except that the polynitrile compound was added according to Table 3 when the electrolyte solution was prepared.
[0074] Examples 4-1 to 4-9 The same as in Example 1-3, except that the sulfur-oxygen double bond-containing compound was added according to Table 4 when the electrolyte solution was prepared.
[0075] Examples 5-1 to 5-7 The same as in Example 1-3, except that the lithium salt additive was added according to Table 5 when the electrolyte solution was prepared.
[0076] Examples 6-1 to 6-4 The same as in Example 1-3, except that at least two of the polynitrile compound, the sulfur-oxygen double bond-containing compound and the lithium salt additive were added according to Table 6 when the electrolyte solution was prepared.
[0077] Examples 7-1 to 7-9 The same as in Examples 1-3, except that the relevant production parameters were adjusted according to Table 7.
[0078] Comparative Example 1 to Comparative Example 3 It was the same as Example 1-1, except that the relevant manufacturing parameters were adjusted according to Table 1. When b was 4 m, the size of the positive electrode piece was adjusted to 65 mm × 4010 mm, and the size of the negative electrode piece was adjusted to 68 mm × 4015 mm.
[0079] Tables 1 to 7 show the manufacturing parameters and performance tests for each of the examples and comparative examples.
[0080] [Table 1]
[0081] As can be seen from Examples 1-1 to 1-16 and Comparative Examples 1 to 3, when b and a / b are within the range of the present invention, the number of cycles of the lithium ion battery increases, which indicates that the cycle performance of the lithium ion battery is improved. At the same time, the number of batteries that pass the overcharge test and the hot box test increases, and the storage thickness expansion rate decreases, which indicates that the safety performance and high temperature performance of the lithium ion battery are improved. Overall, the overall performance of the lithium ion battery in the present invention is improved compared to the lithium ion battery in the comparative example. The mass percentage of the cyclic carbonate generally affects the performance of the lithium ion battery. As can be seen from Examples 1-1 to 1-16, when the mass percentage of the cyclic carbonate is within the range of the present invention, the obtained lithium ion battery has better cycle performance, high temperature performance and safety performance, i.e., better overall performance.
[0082] [Table 2]
[0083] The coating mass C and a / C of the positive electrode layer generally affect the performance of the lithium ion battery. As can be seen from Examples 1-3 and 2-1 to 2-4, when the coating mass C and a / C of the positive electrode layer are within the range of the present invention, the obtained lithium ion battery has good cycle performance, high temperature performance and safety performance, i.e., good overall performance.
[0084] [Table 3]
[0085] As can be seen from Examples 1-3 and 3-1 to 3-11, by adding a polynitrile compound to an electrolyte containing a cyclic carbonate, the cycle performance, high temperature performance and safety performance of a lithium ion battery can be further improved, that is, the overall performance of a lithium ion battery can be further improved. The type and content of a polynitrile compound and the value of d / Dv10 generally affect the performance of a lithium ion battery. As can be seen from Examples 3-1 to 3-11, when the type and content of a polynitrile compound and the value of d / Dv10 are within the range of the present invention, the obtained lithium ion battery has good cycle performance, high temperature performance and safety performance, that is, good overall performance.
[0086] [Table 4]
[0087] As can be seen from Examples 1-3 and 4-1 to 4-9, the electrolyte contains a cyclic carbonate, and then the sulfur-oxygen double bond-containing compound is added to the electrolyte to further improve the cycle performance, high temperature performance, and safety performance of the lithium ion battery, that is, the overall performance of the lithium ion battery can be further improved. The type and content of the sulfur-oxygen double bond-containing compound generally affect the performance of the lithium ion battery. As can be seen from Examples 4-1 to 4-9, when the type and content of the sulfur-oxygen double bond-containing compound are within the range of the present invention, the obtained lithium ion battery has good cycle performance, high temperature performance, and safety performance, that is, good overall performance.
[0088] [Table 5]
[0089] As can be seen from Examples 1-3 and 5-1 to 5-7, the cycle performance, high temperature performance and safety performance of the lithium ion battery can be further improved by adding a lithium salt additive to the electrolyte containing a cyclic carbonate, that is, the overall performance of the lithium ion battery can be further improved. The type and content of the lithium salt additive generally affect the performance of the lithium ion battery. As can be seen from Examples 5-1 to 5-7, when the type and content of the lithium salt additive are within the range of the present invention, the obtained lithium ion battery has good cycle performance, high temperature performance and safety performance, that is, good overall performance.
[0090] [Table 6]
[0091] As can be seen from Examples 1-3 and 6-1 to 6-4, by adding at least two of polynitrile compounds, sulfur-oxygen double bond-containing compounds and lithium salt additives to the electrolyte containing cyclic carbonate, the cycle performance, high temperature performance and safety performance of the lithium ion battery can be further improved, that is, the overall performance of the lithium ion battery can be further improved. As can be seen from Examples 6-1 to 6-4, the polynitrile compounds, sulfur-oxygen double bond-containing compounds and lithium salt additives have a good synergistic effect, and the obtained lithium ion battery has good cycle performance, high temperature performance and safety performance, that is, good overall performance.
[0092] [Table 7]
[0093] As can be seen from Examples 1-3 and 7-1 to 7-9, when element A is contained in the positive electrode active material, the cycle performance, high temperature performance and safety performance of the lithium ion battery can be further improved, that is, the overall performance of the lithium ion battery can be further improved. The type and content of element A generally affect the performance of the lithium ion battery. As can be seen from Examples 7-1 to 7-9, when the type and content of element A are within the range of the present invention, the obtained lithium ion battery has good cycle performance, high temperature performance and safety performance, that is, good overall performance.
[0094] It should be further understood that, in this specification, relational terms such as first and second are used only to distinguish one entity from another, and do not necessarily require or imply that such an actual relationship or order exists between the entities. And, the terms "comprise" and "contain" or any other variant thereof mean non-exclusive inclusions. Thus, a process, method, product, or facility that includes a set of elements not only includes those elements, but also includes other elements not expressly listed, or further includes elements inherent to such process, method, product, or facility.
[0095] Each embodiment in this specification will be described using the relevant form, and the same or similar parts between each embodiment may be referred to each other, and each embodiment will be described by emphasizing the points that differ from other embodiments.
[0096] The above are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.
Claims
1. 1. An electrochemical device comprising a positive electrode strip and an electrolyte, The positive electrode piece includes a positive electrode tab, and the active length b of the positive electrode tab is 0.5 m to 3 m; The electrolytic solution contains a cyclic carbonate, the mass percentage of the cyclic carbonate is a% based on the mass of the electrolytic solution, and the cyclic carbonate contains ethylene carbonate and / or propylene carbonate; the electrochemical device satisfies 13≦a / b≦110; Along a length of the positive electrode piece, the positive electrode piece includes a first edge and a second edge opposite the first edge, There is one positive electrode tab, the distance from the positive electrode tab to the first edge is L1, the distance from the positive electrode tab to the second edge is L2, and the active length b is equal to the maximum of L1 and L2; or an electrochemical device having two positive electrode tabs, the positive electrode tab closer to the first edge is a first positive electrode tab, and the positive electrode tab closer to the second edge is a second positive electrode tab, a distance from the first positive electrode tab to the first edge is L3, a distance from the second positive electrode tab to the second edge is L4, a distance between the first positive electrode tab and the second positive electrode tab is L5, and the working length b is equal to the maximum of L3, L4, and 0.5×L5.
2. 2. The electrochemical device of claim 1, wherein 25≦a≦60 and 14.5≦a / b≦110.
3. 2. The electrochemical device of claim 1, wherein 20≦a / b≦110.
4. The positive electrode piece includes a positive electrode current collector and a positive electrode material layer provided on at least one surface of the positive electrode current collector, The coating mass of the positive electrode layer is C g / 1540.25 mm 2 2. The electrochemical device of claim 1, wherein the electrochemical device satisfies 50≦a / C≦300.
5. 5. The electrochemical device of claim 4, wherein 0.2≦C≦0.
5.
6. The electrolyte contains a polynitrile compound, Based on the mass of the electrolyte, the mass percentage d% of the polynitrile compound is 0.5% to 5%; The electrochemical device of claim 1, wherein the polynitrile compound includes at least one of glutaronitrile, adiponitrile, succinonitrile, crotononitrile, 3-methylbutenenitrile, 1,2-bis(cyanoethoxy)ethane, 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile.
7. The electrolyte solution is At least one of glutaronitrile, adiponitrile, succinonitrile, and 1,2-bis(cyanoethoxy)ethane; At least one of 1,3,5-hexanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, and 1,3,4,6-hexanetetranitrile; The electrochemical device of claim 6 .
8. The positive electrode piece includes a positive electrode active material, 7. The electrochemical device according to claim 6, wherein Dv10 of the positive electrode active material and mass percentage d% of the polynitrile compound satisfy 0.2≦d / Dv10≦4 and 1 μm≦Dv10≦5 μm.
9. the electrolyte contains a sulfur-oxygen double bond-containing compound; Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond-containing compound is 0.01% to 8%; 2. The electrochemical device of claim 1, wherein the sulfur-oxygen double bond-containing compound comprises at least one of 1,3-propane sultone, ethylene sulfate, methylene methane disulfonate, propenyl-1,3-sultone, tetrafluoroethane-beta-sultone, 2,4-butane sultone, 1,4-butane sultone, 1,8-naphthalenesulfonic acid lactone, and ethylene sulfite.
10. the electrolyte includes a lithium salt additive; Based on the mass of the electrolyte, the mass percentage e% of the lithium salt additive is 0.01% to 2%; 10. The electrochemical device of claim 1, wherein the lithium salt additive comprises at least one of lithium difluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, lithium tetraborate, lithium borate, and lithium trifluoromethanesulfonate.
11. The positive electrode piece includes a positive electrode material layer, The positive electrode active material in the positive electrode material layer contains an element A, Based on the mass of the positive electrode active material, the mass percentage of the element A is 0.001% to 2%; The electrochemical device according to any one of claims 1 to 10, wherein the element A includes at least one of Al, B, Cr, Fe, Mg, Na, S, Ti, Zr, Y, Nb, Mo, W, F and P.
12. An electronic device comprising an electrochemical device according to any one of claims 1 to 11.
Citation Information
Patent Citations
Positive electrode and lithium ion secondary battery
JP2018170145A
Non-aqueous electrolyte secondary battery
JP2019145330A
Lithium secondary battery
JP2022518514A
Nonaqueous electrolyte secondary battery
WO2017047353A1
Nonaqueous electrolyte secondary battery
WO2017163932A1